التقويم التربوي في ضوء المقاربة بالكفاءات( إشكالية التطبيق) - فريجة, أحمد; عيساوي, مازيا (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
من اجل المساهمة في تدعيم التحسينات التي مست احد المكونات الرئيسية للمنهاج والمتمثل في التقويم, تحاول هذه المداخلة أن تتناول بالعرض والتمحيص الصعوبات التي أدت إلى تعثر تطبيق الطرق المعتمدة في تقويم الأنشطة التعليمية وفق المقاربة بالكفاءات متخذة من مادة الفلسفة مدارا لذلك. الكلمات المفتاحية:  التقويم التربوي، المقاربة بالكفاءات      In order to contribute to the improvement of the improvements that have been one of the main components of the curriculum, which is the evaluation, this intervention attempts to address the difficulties that led to the failure of the application of the methods adopted in evaluating the educational activities in accordance with the competency approach, taking the philosophy of the course categories.   Keywords: Educational Calendar, Competency Approach